Spiritual competence and education. Among everybody: Symphonic interpretation (Journal of Parents and Teachers, 2012)
Obviously, when talking about integral education, the spiritual competence-intelligence cannot be considered as a simple one, but as the one who establishes a relationship among the others. The human being is spiritual by nature and must learn to cultivate this dimension due to its importance in search for sense of his/her life.  A clarification of concepts such as spirituality, religiosity and confessionality, each one different but complementary, can be deduced from here. This task is symphonic.
Keywords: spiritual competence; Spirituality; religiosity; Confessionality; Competences; Multiple intelligences; Emotional intelligence.